Agrobacterium-Mediated Stable Genetic Transformation of Populus angustifolia and Populus balsamifera - Maheshwari, Priti; Kovalchuk, Igor (Frontiers in Plant Science, 2016)
The present study demonstrates Agrobacterium tumefaciens-mediated stable genetic transformation of two species of Poplar - Populus angustifolia and Populus balsamifera. The binary vector pCAMBIA-Npro-long-Luc containing the luciferase reporter gene was used to transform stem internode and axillary bud explants. Putative transformants were regenerated on selection-free medium using our previously established in vitro regeneration method. Explant type, genotype, effect of pre-culture, Agrobacterium concentration, a time period of infection and varying periods of co-culture with bacteria were tested for the transformation frequency. The highest frequency of transformation was obtained with stem internode explants pre-cultured for 2 days, infected with Agrobacterium culture at the concentration of OD600=0.5 for 10 min and co-cultivated with Agrobacterium for 48 h. Out of the two genotypes tested, P. balsamifera exhibited a higher transformation rate in comparison to P. angustifolia. The primary transformants that exhibited luciferase activity in a bioluminescence assay under the CCD camera when subjected to PCR and southern blot analysis revealed a stable single-copy integration of luc in their genomes. The reported protocol is highly reproducible and can be applied to other species of poplar; it will also be useful for future genetic engineering of one of the most important families of woody plants for sustainable development.